Making growth more environmentally sustainable in Germany - Grant Kirkpatrick; Gernot Klepper; Robert Price (OECD, 2001)
This document analyses German environmental policies, including, among others, discussion of air and water quality policy, use of the waste management hierarchy approach and of voluntary agreements. The German public has been highly sensitive to environmental concerns, leading to many policy initiatives in this area since the early 1980s. Significant environmental improvements have been achieved, using an approach frequently based on detailed regulations, often developed with the close involvement of industry and even individual polluters. There has developed a tendency to relieve some of the heaviest polluters from the most stringent regulation, on the grounds of competitiveness concerns, and some polluting activities receive considerable direct or indirect subsidies; these policies will increasingly make it unnecessarily expensive to meet environmental targets. Objectives need to be defined more clearly and consistently and a less discriminatory approach to taxation and ...
Keywords: 330; Umweltpolitik; Nachhaltige Entwicklung; Wirtschaftswachstum; Luftreinhaltung; Gewässerschutz; Abfallwirtschaft; Ökosteuer; Emissionsrechte; Deutschland